2023
DOI: 10.1186/s40561-023-00240-2
|View full text |Cite
|
Sign up to set email alerts
|

Student engagement during emergency remote teaching: A scoping review

Abstract: Research on student engagement has recently gained popularity as it can address problems such as early dropout and poor achievement. The growing interest in investigating student engagement during the Covid-19 pandemic is reflected in increased publications addressing this topic. However, no review provided research evidence and an overview of existing literature on student engagement during emergency remote teaching (ERT). We reviewed how student engagement studies were undertaken during ERT from three perspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Shemshack and Spector (2020) conducted a systematic review of terminology associated with personalized learning. Yang et al (2023) focused on student engagement in the context of emergency distance learning. Khaldi et al (2023) conducted a systematic literature review on gamification in e-learning in higher education.…”
Section: Research Gap and Study Objectivementioning
confidence: 99%
“…Shemshack and Spector (2020) conducted a systematic review of terminology associated with personalized learning. Yang et al (2023) focused on student engagement in the context of emergency distance learning. Khaldi et al (2023) conducted a systematic literature review on gamification in e-learning in higher education.…”
Section: Research Gap and Study Objectivementioning
confidence: 99%
“…Although, some studies have reported positive changes in students learning performance amid the COVID-19 pandemic 22 , 24 , 26 , it is still largely unknown how these students, who completed part of studies during the restriction, perform in the post COVID era. This study is an attempt to identify potential risk factor affecting students academic performance and predict students at risk of failure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, among other general trends, a primary challenge for students during the pandemic has been the disruption of their study habits. Although, some studies have reported improvement in the academic performance during the COVID-19 restrictions 22 , 24 26 , students getting used to online learning routines might find it even more challenging to perform well in face-to-face learning. Therefore, it is important to analyze students’ academic performance in relation to various potential risk factors after the COVID-19 restrictions, and predict students at risk of academic failure for necessary/timely instructional and administrative interventions which, consequently, helps improving students’ academic efficiency and performance and the efficacy of higher education 27 , 28 .…”
Section: Introductionmentioning
confidence: 99%
“…During the COVID-19, several types of strategies to facilitate student engagement were described as follows: psychological and motivational factors, flexible pedagogy, teacher' s facilitation or technologies, and digital tools (Yang et al, 2023). We opted for online peer-peer mentoring program, synchronous learning, and global digital social learning using information and communication technologies (ICTs).…”
Section: Research On Learningmentioning
confidence: 99%